A Comparison of Morphological Features Between Freshly Collected and Silica Beads-Dehydrated Macroalgal Samples in The Central Great Barrier Reef, Australia - Welem Turupadang (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTAccurate and reliable identification of macroalgae has a crucial role in a range of research relating to the interaction and function of macroalgae in reef ecosystems. The dependency on identifying macroalgae on fresh samples places severe constraints on conducting this research leading to potential biases due to the selection of sites either close to shore or in the vicinity of fully equipped research stations. Therefore, this study aimed to determine if could reliably be used silica bead-dehydrated samples to identify genera characteristics that are only visible in sectioned material. Fresh macroalgal samples were collected at Nelly Bay, compared to Magnetic Island. Materials and sections were to previously collect macroalgal samples and sections dehydrated in silica beads while in the field and reconstituted in filtered seawater for identification. Each sample was identified using histological sections supported with visual tools (photograph, herbaria). In this study, macroalgal identified samples from all species to genus with characteristic features recognizable within both fresh and reconstituted samples. No artifacts were present in reconstituted macroalgal samples compared to freshly collected samples. Therefore, it is suggested that using silica beads as a preservation field method for collecting and identifying macroalgal samples is a suitable and accurate alternative method to the use of fresh samples, which eliminates the time and distance constraints associated with fresh samples.Keywords: Great Barrier Reef, Histological sectioning, Macroalgae identification, Silica-beads preservation, Reconstituted